FAKTOR-FAKTOR PENENTU KEPUTUSAN PEMBELIAN BLACKBERRY DI SEMARANG - Nunung Ghoniyah; Ursila Ani (LPPM STIE DHARMAPUTRA SEMARANG, 2013)
The objective of this study is to analyze the factors which influence customer decision in buying Blackberry in Semarang such culture, family, motivation, brand personality, product quality and prestise. The population of this study is student of colleges. This study used 100 respondent who is collected by accidental sampling. By using PLS, the result showed that motivation, brand personality influenced buying decision significanly. Besides, culture, family, product quality and prestise had no influence with buying decision. Keyword: family, motivation, brand personality, product quality, prestise, buying decision.